Somatic mutational signatures in polyposis and colorectal cancer. (October 2019) - Grolleman, Judith E.; Díaz-Gay, Marcos; Franch-Expósito, Sebastià; Castellví-Bel, Sergi; de Voer, Richarda M.
Abstract: The somatic mutation spectrum imprinted in the genome of a tumor represents the mutational processes that have been active in that tumor. Large sequencing efforts in various cancer types have resulted in the identification of multiple mutational signatures, of which several have been linked to specific biological mechanisms. Several pan-cancer mutational signatures have been identified, while other signatures are only found in specific tissue types. Research on tumors from individuals with specific DNA repair defects has led to links between specific mutational signatures and mutational processes. Studying mutational signatures in cancers that are likely the result of a genetic predisposition may represent an interesting strategy to identify constitutional DNA repair defects, including those underlying polyposis and colorectal cancer.